Human metapneumovirus prevalence during 2019-2021 in Israel is influenced by the COVID-19 pandemic. (July 2022) - Stein, Michal; Cohen, Hodaya; Nemet, Ital; Atari, Nofar; Kliker, Limor; Fratty, Ilana S.; Bucris, Efrat; Geva, Miranda; Mendelson, Ella; Zuckerman, Neta; Mandelboim, Michal
Highlights: We study the impact of COVID-19 on hMPV circulation in Israel between 2019 and 2021. hMPV prevalence in higher in young children was higher and lower in older adults. hMPV infection in 2021 was noticed later compared with previous years. Whole-genome sequencing of hMPV demonstrated a shift from A2b to B2 in 2021. ABSTRACT: Objectives: To compare infection rates and circulating subtypes of human metapneumovirus (hMPV) before (2019-2020) and after the emergence of coronavirus disease 2019 (COVID-19) (2021) in Israel. Methods: In total, 12, 718 respiratory samples were collected from hospitalized patients of all ages during the years 2019 to 2021 at the Sheba Medical Center in Israel and subjected to reverse transcription-polymerase chain reaction analysis. In addition, whole-genome sequencing was performed to characterize the subtypes of hMPV circulating in Israel between 2019 and 2021. Results: A total of 481 samples were found positive for hMPV. Before the emergence of COVID-19, hMPV peaked in winter months and declined thereafter. In sharp contrast, during the COVID-19 pandemic, we observed a delayed peak in hMPV infection cases and higher infection of young children. Viral sequencing showed a shift in the most prevalent circulating hMPV strain from A2b to B1 during the years 2019, 2020, and 2021. Conclusion: Compared with the years before the COVID-19 pandemic, in 2021, hMPV mostly affected young children, and the most prevalent circulating subtype shifted from A2b in 2019 to B1.